The fossil hunter : dinosaurs, evolution, and the woman whose discoveries changed the world - Emling, Shelley (Palgrave Macmillan, 2011)
A biography of nineteenth-century British paleontologist Mary Anning, covering her discovery of an ichthyosaur fossil in England, which laid the groundwork for Darwin's theory of evolution and attracted the attention of the scientific world.